prove that if $\sin^{2}\alpha+\sin^{2}\beta+\sin^{2}\gamma=2$ then the triangle has a right angle.

$\alpha,\beta,\gamma$ are the angles of the triangle.

I tried to use all kinds of trigonometric identities but it didn't work for me. it's to complex form me


  • $\begingroup$ Have you used that $\alpha +\beta +\gamma=\pi?$ $\endgroup$ – mfl May 13 '14 at 19:28
  • $\begingroup$ do you mean: $\alpha +\beta +\gamma=\pi$? and yes i did $\endgroup$ – gorgi May 13 '14 at 19:29
  • $\begingroup$ @AidanF.Pierce - but i need to prove directly.. $\endgroup$ – gorgi May 13 '14 at 19:41

Rearranging, we have $$\sin^2(a) = \cos^2(b) + \cos^2(c)$$ Since $a=\pi-(b+c)$, we get $$\sin^2(b+c) = \cos^2(b) + \cos^2(c)$$ Hence, $$(\sin(b)\cos(c) + \cos(b) \sin(c))^2 = \cos^2(b) + \cos^2(c)$$ This gives us $$\sin(b)\sin(c)\cos(b)\cos(c) = \cos^2(b) \cos^2(c)$$ This means $$\cos(b) \cos(c) = 0 \text{ or }\cos(b+c) = 0$$ Now conclude what you want.


Let $\alpha$, $\beta$ and $\gamma$ be the angles of a triangle; then it holds $$ \boxed{\sin^2\alpha+\sin^2\beta+\sin^2\gamma=2+2\cos\alpha\cos\beta\cos\gamma} $$ If this equals $2$, we conclude $$ \cos\alpha\cos\beta\cos\gamma=0 $$ so one of the angles is a right angle.

Proof of the claim

Let's use that $\gamma=\pi-\alpha-\beta$, so $\cos\gamma=-\cos(\alpha+\beta)$. Then \begin{align} \cos^2\alpha+\cos^2\beta+\cos^2\gamma&= \cos^2\alpha+\cos^2\beta+\cos^2(\alpha+\beta)\\ &=\cos^2\alpha+\cos^2\beta+\cos^2\alpha\cos^2\beta+\sin^2\alpha\sin^2\beta\\ &\qquad-2\sin\alpha\sin\beta\cos\alpha\cos\beta\\ &=\cos^2\alpha+\cos^2\beta+1-\cos^2\alpha-\cos^2\beta+2\cos^2\alpha\cos^2\beta\\ &\qquad-2\sin\alpha\sin\beta\cos\alpha\cos\beta\\ &=1+2\cos\alpha\cos\beta(\cos\alpha\cos\beta-\sin\alpha\sin\beta)\\ &=1-2\cos\alpha\cos\beta\cos\gamma \end{align} giving the final relation $$ \boxed{\cos^2\alpha+\cos^2\beta+\cos^2\gamma=1-2\cos\alpha\cos\beta\cos\gamma} $$ Now \begin{align} \sin^2\alpha+\sin^2\beta+\sin^2\gamma &=3-\cos^2\alpha-\cos^2\beta-\cos^2\gamma\\ &=2+2\cos\alpha\cos\beta\cos\gamma \end{align} as claimed at the beginning.


Using Prove that $\cos (A + B)\cos (A - B) = {\cos ^2}A - {\sin ^2}B$


$$=2-\cos(A-B)\cos(A+B)-\cos C\cos C$$

$$=2-\cos(A-B)\cos(\pi-C)-\cos\{\pi-(A+B)\}\cos C$$

$$=2+\cos(A-B)\cos C+\cos(A+B)\cos C\text{ as }\cos(\pi-x)=-\cos x$$

$$=2+\cos C[\cos(A-B)+\cos(A+B)]$$

$$=2+\cos C[2\cos A\cos B]$$

  • $\begingroup$ @gorgi, How about this? $\endgroup$ – lab bhattacharjee May 14 '14 at 8:24
  • $\begingroup$ im not familiar with the sign $\overline$ but it looks nice. thanks! $\endgroup$ – gorgi May 14 '14 at 23:21
  • $\begingroup$ @gorgi, Sorry for the confusion. Please find the edited version $\endgroup$ – lab bhattacharjee May 15 '14 at 3:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.